Loss of Arid1a Promotes Neuronal Survival Following Optic Nerve Injury - Peng, Xue-Qi; Dai, Shang-Kun; Li, Chang-Ping; Liu, Pei-Pei; Wang, Zhi-Meng; Du, Hong-Zhen; Teng, Zhao-Qian; Yang, Shu-Guang; Liu, Chang-Mei (Frontiers in Cellular Neuroscience, 2020)
Trauma or neurodegenerative diseases trigger the retrograde death of retinal ganglion cells (RGCs), causing an irreversible functional loss. AT-rich interaction domain 1A (ARID1A), a subunit of the SWItch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex, has been shown to play crucial roles in cell homeostasis and tissue regeneration. However, its function in adult RGC regeneration remains elusive. Here, we show that optic nerve injury induces dynamic changes of Arid1a expression. Importantly, deleting Arid1a in mice dramatically promotes RGC survival, but insignificantly impacts axon regeneration after optic nerve injury. Next, joint profiling of transcripts and accessible chromatin in mature RGCs reveals that Arid1a regulates several genes involved in apoptosis and JAK/STAT signaling pathway. Thus, our findings suggest modulation of Arid1a as a potential therapeutic strategy to promote RGC neuroprotection after damage.